Twenty Years of Growth and Innovation: A Reflection on PACKRAT's Impact on Physician Assistant Education. Issue 4 (December 2015) - Cavanagh, Kim; Lessard, Donovan; Britt, Zach
Abstract : Abstract: In its 20th year, the Physician Assistant Clinical Knowledge Rating and Assessment Tool (PACKRAT) is a student self-assessment that can assist physician assistant (PA) students and PA program faculty in identifying strengths and areas in need of improvement in the didactic and clinical phases of PA education. In this reflection, we provide an overview of the history of PACKRAT and outline some of its benefits for students and PA programs, as well as its generative role in assessment within PA studies. Taking a broader view of PACKRAT's impact on assessment for the PA profession, we outline the research on its benefits and its use to maximize student performance, as well as how it has promoted the development of additional assessment tools.